Erratum to ‘‘A New Pre-Order Relation for Set Optimization using $\ell$-difference [Commun. Adv. Math. Sci., 4(3) (2021), 163-170 - Emrah Karaman (Communications in Advanced Mathematical Sciences, 2022)
In this work, an erratum for a proposition in the paper ‘‘A New Pre-Order Relation for Set Optimization using $\ell$-difference" is outlined. It was pointed out by Stefan Rocktäschel and Ernest Quintana that the proof of Proposition 3.11 is wrong in \cite{koc}. A small detail in the proof of Proposition 3.11 has been overlooked. A new proposition, which is closely related to Proposition 3.11 in \cite{koc}, is presented. The main results of the paper are not affected by this erratum.